Labeled PSI from Fully Homomorphic Encryption with Malicious Security - Chen, Hao; Huang, Zhicong; Laine, Kim; Rindal, Peter (ACM SIGSAC Conference on Computer and Communications Security, 2018)
Private Set Intersection (PSI) allows two parties, the sender and the receiver, to compute the intersection of their private sets without revealing extra information to each other. We are interested in the [unbalanced] PSI setting, where (1) the receiver's set is significantly smaller than the sender's, and (2) the receiver (with the smaller set) has a low-power device. Also, in a [Labeled PSI] setting, the sender holds a label per each item in its set, and the receiver obtains the labels from the items in the intersection. We build upon the unbalanced PSI protocol of Chen, Laine, and Rindal (CCS 2017) in several ways: we add efficient support for arbitrary length items, we construct and implement an unbalanced Labeled PSI protocol with small communication complexity, and also strengthen the security model using Oblivious Pseudo-Random Function (OPRF) in a pre-processing phase. Our protocols outperform previous ones: for an intersection of 2^[20] and 512 size sets of arbitrary length items our protocol has a total online running time of just 1 second (single thread), and a total communication cost of 4 MB. For a larger example, an intersection of 2^[28] and 1024 size sets of arbitrary length items has an online running time of 12 seconds (multi-threaded), with less than 18 MB of total communication.